Perceived stress as mediator on the relationship between emotional intelligence and life satisfaction among low-income Malaysians - Mat Din, Hazwan; Mohd Noor, Norhayati; Rasudin, Nur Syahmina; Manoharan, Anusha; Ling, Beatrice Jee Ngee (Elsevier B.V., 2026)
Perceived stress is one of the key psychological factors that influence overall life satisfaction. Low-income individuals are among those who consistently face stress. Emotional intelligence is known to reduce stress and improved wellbeing, yet limited research has been done among low-income populations. This study examined whether perceived stress mediates the relationship between emotional intelligence and life satisfaction among low-income adults in Malaysia. A cross-sectional study was conducted among participants recruited from a public primary healthcare clinic. The study inclusion criteria were Malaysian citizens, literate in Malay, and eligible for the national healthcare access for low-income scheme. Individuals with psychiatric disorders, physical disabilities, or cognitive impairments were excluded. The required sample size was calculated based on guidelines for mediation analysis with bootstrapping, taking into account non-response. Validated questionnaires in Malay language were administered. Mediation analysis was performed using the PROCESS Macro, controlling for age and ethnicity. A total of 427 participants were recruited, with a mean age of 62.1 (9.19) years, ranging from 40 to 83 years old. Results showed that individuals with higher emotional intelligence reported lower perceived stress, and those with lower stress reported greater life satisfaction. Perceived stress partially mediated this relationship. It suggests that emotional intelligence may shape life satisfaction by altering how stress is perceived and managed. These findings highlight the importance of emotional intelligence as a protective psychological resource in enhancing wellbeing among low-income adults. Interventions aimed at building emotional competencies could serve as a valuable addition to broader strategies addressing mental health and wellbeing in low-income populations.